Vida e obra do escultor António Paiva : levantamento da obra artística - Sequeira, Joana Paiva de Menezes de (2022)
This investigation deals with the life and work of the Portuguese sculptor António Paiva and is not a monography. António Paiva can be considered a sculptor of the second modernism, as he seeks to counteract residual academic standards2. Thus, the starting point was the contextualization of the life and work of this sculptor, both historically and politically, as well as artistically and biographically. António Paiva's life is intrinsically relatedto his sculptures, in the sense that it is possible to understand, through his analysis, the critical gaze of the author and his choices. It was through the analysis of some of his sculptures that we were able to establish the causality index between the artist's life and work. Given the extent of the work found, we opted for a typological classification, pre-defined in the workby Marie Thérese Baudryet. At the same time and to disseminate António Paiva's sculptural work, we decided to create a second volume of this dissertation with all the inventory of the work found. It is on these sheets that we gather the images of the sculptures and all the technical information corresponding to each one